The relationship between human resources management practices and employee performance in electrical and electronics manufacturing industries - Shashveena Thevi, Venu Goball (2024)
The purpose of this research is to study the relationship between human resources management practice (training and development, performance appraisal, reward and recognition) and employee performance in electrical and electronical industries. Data was collected through questionnaires from 210 employees working in manufacturing companies located in four Malaysian states: Penang, Johor, and Selangor. Quantitative approach has been used in this study through questionnaire and online distribution for data collection. the data were analysed using for four analyses which are reliability test, descriptive analysis, mean analysis, correlation analysis. The results show the significance of human resource management (HRM) practices in predicting employee performance. This chapter discuss the implications of these findings for HRM practise and offer recommendations for developing effective HRM strategies to enhance employee performance